2014
DOI: 10.1063/1.4869459
|View full text |Cite
|
Sign up to set email alerts
|

Highly polarized photoluminescence and its dynamics in semipolar (202¯1¯) InGaN/GaN quantum well

Abstract: Very high polarization degree of 0.98, considerably larger than theoretical predictions, has been measured in (202¯1¯) In0.24Ga0.76N/GaN quantum well by low temperature photoluminescence. With increasing temperature, the polarization degree decreases due to thermal population of the excited valence band level. This effect suggests an accurate method to determine the interlevel energy, which, for the studied well, is 32 meV. Time-resolved photoluminescence measurements set radiative recombination times between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This has also been observed on InGaN/GaN MQWs grown on free-standing GaN substrates. [9][10][11][12][13] A standard two exponential component model is used to study excitonic dynamics, and thus TRPL traces [I(t)] can be described by [16][17][18] IðtÞ ¼ A 1 expðÀt=s 1 Þ þ A 2 expðÀt=s 2 Þ:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been observed on InGaN/GaN MQWs grown on free-standing GaN substrates. [9][10][11][12][13] A standard two exponential component model is used to study excitonic dynamics, and thus TRPL traces [I(t)] can be described by [16][17][18] IðtÞ ¼ A 1 expðÀt=s 1 Þ þ A 2 expðÀt=s 2 Þ:…”
mentioning
confidence: 99%
“…Such a systematic study on ð11 22Þ semipolar InGaN/GaN MQW with high indium content has not yet been reported, even on very expensive free-standing semipolar GaN substrates. [9][10][11][12][13][14]21 The ð11 22Þ semi-polar GaN has been obtained by overgrowth on nanorod templates, which were fabricated using our self-organized nickel nano-mask technique. 6,7 Four samples, each with five periods of InGaN/GaN MQWs were grown on the overgrown ð11 22Þ GaN.…”
mentioning
confidence: 99%
“…Previous standard PL studies related lower DLP in long wavelength tails to confined exciton states of zero-dimensional symmetry [41] and inclusions of a semipolar phase [22]. Our near-field data suggest that these regions should rather be associated with areas with a partial strain relaxation (presumably, around dislocations), because the low DLP areas are few, and the DLP in these spots is much lower than expected for the semipolar phases [23,42]. Besides, in these regions the peak wavelength is longer, as should be expected for strain-relaxed regions.…”
Section: E Spectral Dependence Of Pl Polarizationmentioning
confidence: 46%
“…The largest DLP value is as high as 0.98, showing that the transition is fully polarized, as suggested by the calculations for ideal bands without the band potential fluctuations [34]. The main peak DLP is close to the largest values measured for nonpolar and semipolar InGaN QWs [29,[33][34][35] at low temperatures, at which thermal population of the 2nd valence band level is negligible.…”
Section: Morphology (Nm)mentioning
confidence: 50%
“…Clearly, the symmetry properties of these states are different from those of the ideal bands. Our near-field data suggest that these regions might be related to the strain relaxation around dislocations because the DLP is much lower than expected for the semipolar phase inclusions [35,36]. Besides, in these areas the peak wavelength is longer, as should be expected for the strain-relaxed regions.…”
Section: Morphology (Nm)mentioning
confidence: 75%